Moving beyond visitor satisfaction to loyalty in nature-based tourism: a review and research agenda - Moore, S.; Rodger, K.; Taplin, Ross (Routledge, 2014)
Nature-based tourism is increasing worldwide and with it the opportunity to engage these visitors to support and advocate for the protection of natural areas. Loyalty research over the last decade provides a platform for action. Analysing loyalty as an important focus for nature-based tourism research and then proposing a research agenda are the aims of this paper. These aims are achieved by (1) reviewing the place of satisfaction and its relationship to loyalty in nature-based tourism research; (2) analysing recent loyalty and related behavioural intentions research; and (3) proposing a research agenda to further progress loyalty research. Conducting field-based experiments to determine the influence of improving service quality on loyalty and further investigating a suite of items of varying commitment for measuring loyalty (from recommending a destination to others to volunteering to work there) are pivotal to the proposed agenda. Also central are further elaborating and testing the measurement model for loyalty, with place attachment and pursuit of benefits, such as escaping from everyday life and appreciating nature, suggested as promising antecedents to loyalty. The importance of natural areas to society warrants urgent attention to the loyalty-centred research agenda detailed in this paper.